Analisis Kepuasan Pasien Terhadap Pelayanan Kefarmasian di Apotek Icha Farma Kabupaten Sidrap - Nurlaela Nurlaela; Reny Anggriany Hakim; Mutmainna Tajuddin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Pharmaceutical service is a diect and responsible service to patients, which is related to pharmaceutical preparations with the aim of achieving optimal results to improve the quality of patient health. Satisfaction is a person's feeling of pleasure or not that comes from the comparison between the pleasure of an activity and a product with his expectations, the factors used to measure the level of patient satisfaction are the elements of reliability, responsiveness, assurance, empathy ( empathy), Facilities (tangible). This study aims to determine the level of patient satisfaction in pharmaceutical services on five dimensions, the type of research carried out is descriptive research. The results of the study show that the analysis of patient satisfaction in pharmaceuntical services at Icha Farma Pharmacy is satisfied.